Public Private Partnership, Policy Implementation and Service Delivery in Rivers State: A Study of Greater Port Harcourt, 2009 2025 - ThankGod Chima Nwafor (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The thrust of this paper is to examine public private partnership, policy implementation and service delivery in Rivers State: A study of greater Port Harcourt, 2009-2025. global movement for the transformation of governance has brought about sundry innovations in public administration. One of such innovations is the Public-Private Partnership (PPP), which is fast becoming an attractive menu in the list of global best practices. The initiative recognises the potency of the private sector in the good governance project, and therefore seeks to encourage the synergy between the private sector and the public sector for improved service delivery. In Rivers State, the urgent need to arrest the continuing delay in achieving the goal of the greater Port Harcourt has compelled the government to key into this approach. Public-private partnership in greater Port Harcourt is expected to improve policy implementation and enhance service delivery. The paper employed the correlational approach. The study recommends that the design and execution of projects outlined in the greater Port Harcourt plan should be discussed and voted on to ensure that they reflect the needs of the people as citizen engagement in the plan implementation will infuse a sense of ownership in the people and encourage them to monitor the progress of the implementation if government enacts efficient policies and regulations to create an enabling environment for all stakeholders to participate in the provision of social housing.